Tussilagone Suppresses Angiogenesis by Inhibiting the VEGFR2 Signaling Pathway - Jia Li; Jia Li; Jiangtong Peng; Jiangtong Peng; Shengnan Zhao; Shengnan Zhao; Yi Zhong; Yi Zhong; Yilong Wang; Yilong Wang; Ji Hu; Ji Hu; et al. (Frontiers Media S.A., 2019)
Tussilagone (TSL) is a sesquiterpenoid isolated from Tussilago farfara, which has been used as a traditional medicine for the treatment of asthma and bronchitis. It also takes part in the anti-inflammatory and antioxidant effects, but its role in angiogenesis is unknown. Angiogenesis is a cancer feature that is essential for supplying oxygen and nutrients to all proliferating tumor cells. Here, we demonstrated that TSL significantly inhibited the proliferation, migration, invasion, and tube formation of primary human umbilical vascular endothelial cell (HUVEC) in vitro. Also, TSL inhibited vascular endothelial growth factor (VEGF)-induced angiogenesis revealed by Matrigel plug assay in vivo. At present, we observed that TSL inhibited the activity of VEGFR2 signal pathway induced by VEGF. These findings suggested that TSL may serve as a potential therapeutic target in the angiogenesis.